Flexural strength and ductility of moso bamboo. (20th June 2020) - Chen, Meiling; Ye, Ling; Li, Hui; Wang, Ge; Chen, Qi; Fang, Changhua; Dai, Chunping; Fei, Benhua
Highlights: An original approach was proposed to assess the flexural ductility of bamboo. Flexural strength and ductility of moso bamboo were higher than those of wood with similar density. There was a conflicting relationship between flexural strength and ductility in bamboo. Abstract: Bamboo is a fast growing and natural fiber-reinforced material with excellent flexural strength and ductility. While it has been increasingly used in many applications, flexural ductility of bamboo and methods to evaluate this property have not been fully investigated. This paper proposed an original approach to assess the flexural ductility of bamboo and presented a number of reasons why bamboo outperforms wood in this aspect. Results showed that bamboo had significantly higher flexural ductility, better strength properties but moderately lower elasticity than wood. At similar density, the flexural ductility and modulus of rupture of bamboo were 3.06 and 1.72 times that of wood, respectively. On the other hand, the modulus of elasticity was 0.84 times that of wood. The flexural strength of bamboo was positively correlated to the vascular bundle content, whereas the flexural ductility was directly correlated to the parenchyma content. There existed a conflicting relationship between the flexural strength and ductility in bamboo. This work contributes to critical knowledge surrounding the flexural strength and ductility of bamboo as a sustainable building construction material.